Comparative study of mangrove composition and diversity in Kudat and Pitas, Sabah - Audrey Adella Eliseus (2012)
The objectives of this study were to compare the floral diversity, species composition of mangrove plants species and compare the natural regeneration between disturbed and undisturbed mangrove forest in Kudat and Pitas, Sabah. The most common mangrove species identified were Rhizophora apiculata, Rhizophora mucronata, Sonneratia caseolaris, Ceriops tagal and Avicennia marina. A total of 120 plots were established; each with the size of 10 x 10m with total area of 12 ha. There were 3 belt transects established randomly with each of them consists of 10 subplots respectively. The highest Important Value Index (IVI) recorded in undisturbed mangrove area in Kudat was Rhizophora apiculata with 211.75 % while Sonneratia caseolaris is the highest recorded in Pitas with 92.54 %. The highest IVI recorded in disturbed area in Kudat was Rhizophora apiculata with 67.68 % while 91.89 % Sonneratia caseolaris recorded in disturbed area in Pitas. The Cj value for disturbed and undisturbed area in Kudat was 0.68 while 0.74 in Pitas. Less similarity of mangrove species found in these areas. The Cj value for undisturbed area in Kudat and Pitas was 0.18 while 0.12 in disturbed area in Kudat and Pitas. More similarity of mangrove species found in these areas. The number of regeneration per hectare in undisturbed mangrove area in Kudat and Pitas also recorded lower number with only 601.7 and 803.3 compared to 2358.3 and 1473.3 in disturbed mangrove area in Kudat and Pitas. The small number of regeneration in undisturbed area in Kudat and Pitas could be the shading effects created by parental canopy that prevent light from reaching the ground.